N= -16.5
Subtract 33 then divide by 2
2n=-33
n=-33/2 or n=-16.5
Answer:
Step-by-step explanation:
For example, if f(x) = 2x + 7
then f(-3) = 2(-3) + 7
f(-3) = 1
The answer is 10 ..............................
Y=mx+b, m=(y2-y1)/(x2-x1)
m=(7-4)/(6--3)=3/9=1/3
y=x/3 +b, now use either point to solve for b, I'll use (6,7)
7=6/3 +b
7=2+b
b=5 so our line is:
y=x/3 +5 or more neatly...
y=(x+15)/3
Answer:
18
Step-by-step explanation:
because the number of people that can swim will be about quarter out of hundred